SIBELIUS-DARK: a galaxy catalogue of the local volume from a constrained realization simulation. Issue 4 (8th February 2022) - McAlpine, Stuart; Helly, John C; Schaller, Matthieu; Sawala, Till; Lavaux, Guilhem; Jasche, Jens; Frenk, Carlos S; Jenkins, Adrian; Lucey, John R; Johansson, Peter H
ABSTRACT: We present sibelius-dark, a constrained realization simulation of the local volume to a distance of 200 Mpc from the Milky Way. sibelius-dark is the first study of the ' Simulations Beyond The Local Universe ' (sibelius ) project, which has the goal of embedding a model Local Group-like system within the correct cosmic environment. The simulation is dark-matter-only, with the galaxy population calculated using the semi-analytic model of galaxy formation, galform . We demonstrate that the large-scale structure that emerges from the sibelius constrained initial conditions matches well the observational data. The inferred galaxy population of sibelius-dark also match well the observational data, both statistically for the whole volume and on an object-by-object basis for the most massive clusters. For example, the K -band number counts across the whole sky, and when divided between the northern and southern Galactic hemispheres, are well reproduced by sibelius-dark . We find that the local volume is somewhat unusual in the wider context of ΛCDM: it contains an abnormally high number of supermassive clusters, as well as an overall large-scale underdensity at the level of ≈5 per cent relative to the cosmic mean. However, whilst rare, the extent of these peculiarities does not significantly challenge the ΛCDM model. sibelius-dark is the most comprehensive constrained realization simulation of the local volume to date, and with this paper we publicly release the halo and galaxy catalogues at z  = 0, which we hope will be useful to the wider astronomy community.